К систематике бычков Черного и Азовского морей - Замбриборщ, Ф.С. (Вестник зоологии, 1968)
The article shows that the present systematics of Gobiidae of the Black and Azov Seas does not satisfy the up-to-date state of studying this fish group. It is very difficult to identify the species of this family, which results from insufficient, sometimes erroneous diagnoses. On the basis of more specified and completed diagnoses a new identification table is presented of 11 genera and 25 species of gobies of the basins of the Black and Azov Seas. The table re-establishes the genera Neogobius and Mesogoleius; the genus Relicto-gobius is replaced by the genus Chromogobius; the genus Pomatoschistus caucasicus is attributed to the genus Knipowitschia, and P. pictus is excluded from the list of the species of the seas in question.